2019
DOI: 10.1007/s10490-019-09651-7
|View full text |Cite
|
Sign up to set email alerts
|

Information diversity and innovation for born-globals

Abstract: Does being a born-global make a startup more or less likely to quit before launch, and how do innovativeness and information diversity affect the decision to start or stop a born-global venture? Born-globals, new ventures that are global from the start, simultaneously create new businesses and enter new markets, whereas firms that do not choose to start as born-globals face only the challenges of creating a new business. We examine how new ventures, both born-globals and non-born-globals, address these challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 71 publications
(171 reference statements)
2
10
0
1
Order By: Relevance
“…Hypothesis 3 focuses on the impact of the ownership structure of the LSPs on survival. At the 5% level of significance, the exit risk of foreign-owned LSPs is nearly half of domestic-owned, after controlling for other variables, which shows that foreign-owned LSPs have better survival prospects, which echoes with the findings of Hull, et al [46]. The possible explanation is that the foreign-owned LSPs located in the suburbs is lower than that of urban LSPs, especially for small-scale ones (1% significance level).…”
Section: Model Adjustment and Analysis Resultssupporting
confidence: 59%
“…Hypothesis 3 focuses on the impact of the ownership structure of the LSPs on survival. At the 5% level of significance, the exit risk of foreign-owned LSPs is nearly half of domestic-owned, after controlling for other variables, which shows that foreign-owned LSPs have better survival prospects, which echoes with the findings of Hull, et al [46]. The possible explanation is that the foreign-owned LSPs located in the suburbs is lower than that of urban LSPs, especially for small-scale ones (1% significance level).…”
Section: Model Adjustment and Analysis Resultssupporting
confidence: 59%
“…From the four above-mentioned studies, Kahiya [20] predicted which firms would become international new ventures, Lautanen [21] studied which firms would start exporting within four years, while Hull et al [19] found out which firms would wish to become born globals. Finally, Baum et al [18] tried forecasting whether a firm would become a born global, a born-again global, a traditional (slow) internationalizer, or a born regional (for an overview of the meanings of these terms, see Appendix I).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several variables have been used for predicting future exporter types. The studies that focused on predicting early internationalization used international growth orientation, learning orientation, product differentiation, prior international experience and strength of network contacts [18], information diversity and being innovative [19], export barriers [20] and firm size, language skills, education, perceived risk, and previous export experience [21] as predictors. The studies that predicted other exporter type related characteristics used an even wider range of variables: for example, economic environment, export market size, firms' organizational policies, business abilities and skills, export strategy, product characteristics, productivity, and time spent on doing international business (see Table I).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferraris et al. , 2017, 2020), while the few on SMEs supports the argument that knowledge and information diversity improves innovative performance and establishes the basis for robust organizational learning capabilities (Hull et al. , 2020; Love et al.…”
Section: Introductionmentioning
confidence: 77%